1969
DOI: 10.1016/s0006-3495(69)86446-5
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold Oscillatory Responses of the Hodgkin-Huxley Cable Model for the Squid Giant Axon

Abstract: The classical cable equation, in which membrane conductance is considered constant, is modified by including the linearized effect of membrane potential on sodium and potassium ionic currents, as formulated in the Hodgkin-Huxley equations for the squid giant axon. The resulting partial differential equation is solved by numerical inversion of the Laplace transform of the voltage response to current and voltage inputs. The voltage response is computed for voltage step, current step, and current pulse inputs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…Phenomenological inductances (alternately called resonating conductances) are contributed by conductances that actively oppose changes in membrane voltage (Cole, 1968;Sabah and Leibovic, 1969;Hutcheon and Yarom, 2000). The functional expression of a phenomenological inductance is not only dependent on the kinetics and voltage dependence of the mediating ion channel, but also on the passive properties of the membrane they reside in (Table 1).…”
Section: Inductive Phase Is Dependent On Passive and H-channel Propermentioning
confidence: 99%
See 1 more Smart Citation
“…Phenomenological inductances (alternately called resonating conductances) are contributed by conductances that actively oppose changes in membrane voltage (Cole, 1968;Sabah and Leibovic, 1969;Hutcheon and Yarom, 2000). The functional expression of a phenomenological inductance is not only dependent on the kinetics and voltage dependence of the mediating ion channel, but also on the passive properties of the membrane they reside in (Table 1).…”
Section: Inductive Phase Is Dependent On Passive and H-channel Propermentioning
confidence: 99%
“…It was later demonstrated that these inductive reactances as well as their capacitive counterparts emerge because of the presence of voltage-dependent, time-variant conductances (Mauro, 1961;Cole, 1968;Sabah and Leibovic, 1969;Mauro et al, 1970), and such reactances have been variously named as "anomalous" (Cole, 1949) or "phenomenological" reactances (Mauro et al, 1970;Koch, 1984). Importantly, whereas excitatory conductance changes contribute to a capacitive reactance, conductance changes that aid in membrane recovery yield an inductive reactance (Cole, 1968;Sabah and Leibovic, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…This approach relies on linearizing voltage-dependent cable conductances around the membrane potential V R . The method was first employed by Sabah and Leibovic (1969) and further worked on by Koch (1984), and it elucidates certain general principles of quasi-active cables. This approach allowed classifying I NaP as a regenerative current, which produces a positive feedback and amplifies membrane potential changes, boosting and broadening excitatory postsynaptic potentials (EPSPs).…”
mentioning
confidence: 99%
“…The response of the system for small signal stimulus is calculable, and compares well with experiment [9,10].…”
mentioning
confidence: 57%
“…Time, milliseconds m = ma{v)] h = h"(v = 0), n = na{v = 0), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and the resulting wave form for v and m is a step instead of a pulse, as shown in Fig. 1.4.…”
mentioning
confidence: 99%